2014
DOI: 10.1186/1746-6148-10-27
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of veterinarians and producers concerning Johne’s disease prevalence and control in US beef cow-calf operations

Abstract: BackgroundEfforts to educate producers and veterinarians in the United States regarding the management, prevention and control of Mycobacterium avium subspecies paratuberculosis (MAP) infection have increased over recent years. While nationwide awareness about MAP infection is improving, current level of awareness among beef producers and veterinarians is largely unknown. This study compares the perceptions of beef producers and veterinarians on the burden of MAP infection in cow-calf herds and on measures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Thus, although comparable data are not available from European countries, the perception of PTB and the motivation of dairy farmers toward control measures appear to be similar across countries and continents. Similar perceptions and motivations have been described for beef farmers in North America as well [27,28].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, although comparable data are not available from European countries, the perception of PTB and the motivation of dairy farmers toward control measures appear to be similar across countries and continents. Similar perceptions and motivations have been described for beef farmers in North America as well [27,28].…”
Section: Discussionsupporting
confidence: 63%
“…Economic considerations can also be a motivator for implementing management changes, depending on the awareness of the farm manager about the economic impact of the disease. Several authors have reported that the losses associated with PTB are often underestimated by farmers [ 12 , 28 , 30 ]. In small herds as in our study, the number of clinical cases on the farm and, therefore, the directly visible losses due to PTB may be relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show a prevalence of above 50% for MAP in dairy herds in countries operating intensive farming systems [ 40 ] with low levels (5%) of clinical disease [ 44 ]. Indeed, in the United States, prevalence ranges from 68 to 91% in dairy herds and 8% of beef herds [ 45 ] with estimates typically based on ELISA, fecal culture, or PCR techniques. Estimating prevalence of infection is difficult as identification of MAP is achieved mostly via fecal culture, with no symptoms of infection in the animal subclinically.…”
Section: Prevalence Of Diseasementioning
confidence: 99%
“…The private veterinary practitioner (PVP) is considered an important source of information for farmers on disease control generally 1–3 . Although herd PVPs may actively engage with their clients on JD control strategies, the effectiveness of this engagement and the potential for compliance with control measures can be undermined by a lack of PVP training and confidence in specific JD epidemiology 4 5 . A number of countries including Canada, the UK and the Netherlands currently have JD control programmes that involve PVP training and direct farmer engagement, and in which on‐farm risk assessment forms a central component 6 .…”
Section: Introductionmentioning
confidence: 99%